PENTINGNYA MERUMUSKAN VISI DAN MISI PADA LEMBAGA PENDIDIKAN - Aulia, Yenni; Ose, Fitria; Idris, Idris; Rusdinal, Rusdinal; Anisah, Anisah (STKIP Pesisir Selatan, 2024)
This research aims to summarize and describe the importance of formulating a vision and mission in educational institutions. The method used in writing this scientific article is by using the library research method. In an educational institution, the vision and mission are very important. The vision and mission of an educational institution is the foundation that serves as a guide for all stakeholders, from managers, teaching staff, to students. The vision reflects the image of the future desired by the institution, while the mission describes the concrete steps that will be taken to realize that vision. Therefore, the success of an organization is largely determined by the process of formulating the vision and mission of the educational institution. Formulating a vision and mission also plays a key role in increasing the accountability of educational institutions. By setting specific goals in the mission, institutions have a basis for measuring their performance and achievements. This helps create high standards of quality and accountability, which in turn contributes to improving the overall quality of education. Schools must carry out their duties well as educational institutions whose mission is to achieve educational goals. In recognizing its role as an educational institution, schools must be managed well to achieve the formulated educational goals optimally without hesitation